Sanksi Hukum Adat terhadap Kejahatan Pembunuhan di Desa Rantau Limau Manis Perspektif Hukum Islam - Salman, Salman; Bintang, Amar (Legalitas: Jurnal Hukum, 2024)
The aplication of customary criminal law in Rantau Limau Manis Village has been in effect since the village`s estbilishment, with its customary law based on Islamic syariah, as evidenced by the customary saying: “adat basendi syara`, syara` basendi Kitabullah.” Murder is categoryzed as a serious crime under the village`s customary law, which is reflected in the imposition on the heaviest sanctions on the perpetrator, namely the punishment of “bangun” involving the payment of a buffalo along with rice, coconuts, wgite cloth, and spices for cooking. The specipics of these materials correspond to the severity of the murder comitted. Similiarly, in Islamic criminal law, murder is also classified as a serious offense, punishable by qisas (retaliation) and diat (blood money). For intentional murder, the perpetrator faces qisas if there is no forgiveness from the victim`s family. In cases of unintentional murder and intentional murder, the perpetrator is subject to the diat penalty.